The Correlation Between Students’ Learning Styles And Students’ Writing Achievement - Agusta, Okky Leo (Linguists : Journal of Linguistics and Language Teaching, 2019)
The objectives of this research were to find out the percentages of students’ learning styles and find out the relationship between students’ learning styles and students’ writing achievement. The method was used by this research was correlation research to find out the correlation between two variables. The population of this research was all of the tenth grade students in vocational school Tugumulyo, Musi Rawas, South Sumatera. The sample was otomotive engineering class and the class consisted 31 students. To get students’ learning style, the researcher used learning style inventory with questionnaire and to get students’ writing achievement, the researcher used writing test. Then, the technique for analyzing the data was the percentage calculation and Person Product Moment to find out the correlation between students’ learning style and students’ writing achievement. The findings, the students were 39% visual learning style, 42% Auditory learning style, and 19% Kinesthetic learning style. The coeffecient relationship robtained was -0.280 ( robtained < rtable ), there was no significant relationship between students’ learning style and students’ writing achievement.